2014
DOI: 10.4028/www.scientific.net/amr.919-921.1880
|View full text |Cite
|
Sign up to set email alerts
|

Crack Self-Healing Properties of Concrete with Adhesive

Abstract: An experimental program was carried out to investigate whether EVA (ethylene vinyl acetate) heat-melt adhesive can potentially act as a self-healing agent in cement-based material. The effects of incorporation of EVA and heating on the properties of mortar were studied. Experimental results show that the interface between EVA and cement matrix was well improved after heating, which allows a significant improvement in flexural strength and toughness of specimen; Pre-damaged specimens in various degrees (30%, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The extent of flexural and CS, as well as other mechanical properties, recovery was tested and assessed (Table 2). Toughness and split TS assessments form a part of these tests [86][87][88]. Various studies reported that UPV and water permeability assessments form a part of these tests [89,90].…”
Section: Macrostructures Evaluationmentioning
confidence: 99%
“…The extent of flexural and CS, as well as other mechanical properties, recovery was tested and assessed (Table 2). Toughness and split TS assessments form a part of these tests [86][87][88]. Various studies reported that UPV and water permeability assessments form a part of these tests [89,90].…”
Section: Macrostructures Evaluationmentioning
confidence: 99%
“…Besides conducting compressive and flexural tests [45,96,97], the performance of concrete has also been assessed by other mechanical tests such as split tensile and toughness tests [98,99] and stiffness tests [100]. Detection of crack initiation and its degree have been carried out using nondestructive complementary tests such as acoustic emission analysis [101], linear variable differential transformer [102] and ultrasonic pulse velocity [103,104].…”
Section: Characterization Of Self-healing Concretementioning
confidence: 99%
“…Self-healing cement has been widely used in many fields. Studies have shown that: self-healing cement can improve the mechanical properties (hardness, strength) and permeability of cement materials [3] , and can repair defects in building materials [4] .…”
Section: Introductionmentioning
confidence: 99%